Associations of Sperm mtDNA Copy Number, DNA Fragmentation Index, and Reactive Oxygen Species With Clinical Outcomes in ART Treatments - Shi, Wei-Hui; Ye, Mu-Jin; Qin, Ning-Xin; Zhou, Zhi-Yang; Zhou, Xuan-You; Xu, Nai-Xin; Chen, Song-Chang; Li, Shu-Yuan; Xu, Chen-Ming (Frontiers in Endocrinology, 2022)
Recent studies have suggested sperm mitochondria DNA copy number (mtDNA-CN), DNA fragmentation index (DFI), and reactive oxygen species (ROS) content are crucial to sperm function. However, the associations between these measurements and embryo development as well as pregnancy outcomes in assisted reproductive technology (ART) remain unclear. Semen samples of 401 participants were collected. Seminal quality, parameters of sperm concentration, motility and morphology, were analyzed by a computer-assisted sperm analysis system. DFI, mtDNA-CN, and ROS levels were measured using real-time quantitative polymerase chain reaction method, sperm chromatin structure assay and Reactive Oxygen Species Assay Kit, respectively. Among the participants, 126 couples were performed with assisted reproductive technology (ART) treatments, including in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI), and 79 of them were transferred embryos. In 401 semen samples, elevated mtDNA-CN and DFI were associated with poor seminal quality. In 126 ART couples, only mtDNA-CN was negatively correlated with the fertilization rate, while this correlation disappeared after adjusting male age, female age, seminal quality, and ART strategy, number of retrieved oocytes, and cycle rank. With regard to pregnancy outcomes, none of sperm mtDNA-CN, ROS and DFI was associated with the clinical pregnancy rate and live birth rate in 79 cases transferred embryos. In conclusion, increased mtDNA-CN and DFI in sperms jointly contributed to poor seminal quality. However, none of sperm mtDNA-CN, ROS and DFI were associated with clinical outcomes in ART.